Postoperative Infectious Complications Worsen Long-Term Survival After Curative-Intent Resection for Hepatocellular Carcinoma - Wei, T (2021)
Background: Postoperative infectious complications may be associated with a worse long-term prognosis for patients undergoing surgery for a malignant indication. The current study aimed to characterize the impact of postoperative infectious complications on long-term oncologic outcomes among patients undergoing resection for hepatocellular carcinoma (HCC). Methods: Patients who underwent curative-intent resection for HCC between 2000 and 2017 were identified from an international multi-institutional database. The relationship between postoperative infectious complications, overall survival (OS), and recurrence-free survival (RFS) was analyzed. Results: Among 734 patients who underwent HCC resection, 269 (36.6%) experienced a postoperative complication (Clavien-Dindo grade 1 or 2 [n = 197, 73.2%] vs grade 3 and 4 [n = 69, 25.7%]). An infectious complication was noted in 81 patients (11.0%) and 188 patients (25.6%) had non-infectious complications. The patients with infectious complications had worse OS (median: infectious complications [46.5 months] vs no complications [106.4 months] [p < 0.001] and non-infectious complications [85.7 months] [p < 0.05]) and RFS (median: infectious complications [22.1 months] vs no complications [45.5 months] [p < 0.05] and non-infectious complications [38.3 months] [p = 0.139]) than the patients who had no complication or non-infectious complications. In the multivariable analysis, infectious complications remained an independent risk factor for OS (hazard ratio [HR], 1.7; p = 0.016) and RFS (HR, 1.6; p = 0.013). Among the patients with infectious complications, patients with non-surgical-site infection (SSI) had even worse OS and RFS than patients with SSI (median OS: 19.5 vs 70.9 months [p = 0.010]; median RFS: 12.8 vs 33.9 months [p = 0.033]). Conclusion: Infectious complications were independently associated with an increased long-term risk of tumor recurrence and death. Patients with non-SSI versus SSI had a particularly worse oncologic outcome.